2019
DOI: 10.1080/03605302.2019.1581803
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness results for Zakharov-Kuznetsov equation

Abstract: In this paper we study uniqueness properties of solutions to the Zakharov-Kuznetsov equation of plasma physic.Given two sufficiently regular solutions u 1 , u 2 , we prove that, if u 1´u2 decays fast enough at two distinct times, then u 1 " u 2 .The equation was introduced in the context of plasma physic by Zakharov and Kuznetsov in [38], where they formally deduced that the propagation of nonlinear ion-acoustic waves in magnetized plasma is governed by this mathematical model. A rigorous derivation of equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…3/2. This claim found support and confirmation in [4] where the following unique continuation principle was obtained for the symmetric ZK equation (4).…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…3/2. This claim found support and confirmation in [4] where the following unique continuation principle was obtained for the symmetric ZK equation (4).…”
Section: Introductionsupporting
confidence: 56%
“…In this work we are mainly interested in the unique continuation setting of problems linked to the equation. At this regard we should mention the recent work [4]. The main achievement in [4] has been to obtain sharp sufficient conditions on the (spatial) decay of the difference of two solutions of (1) at two different times which guarantee that both solutions coincide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in this direction, in [2], for the Ostrovsky equation and in [3], for the Zakharov-Kuznetsov (ZK) equation, Bustamante et al, showed that if the difference of two sufficiently regular solutions u 1 and u 2 have a suitable decay in two different times, then they are equal. Recently, the results in [3] was improved in [6].…”
Section: Introductionmentioning
confidence: 99%